ANALISIS RETURN SAHAM DAN TVA PADA SEKTOR KESEHATAN SEBELUM DAN SELAMA PANDEMIK COVID-19 - Fissholah, Qurrota Aini; Hascaryani, Tyas Danarti (Contemporary Studies in Economic, Finance and Banking, 2022)
The existence of the COVID-19 pandemic at the end of 2019 greatly affected various sectors, one of which affected the conditions on the capital market sector in Indonesia. This research aims to determine and analyze comparisonal in stock return and Trading volume activity (TVA) between before and during the covid-19 pandemic in Indonesia. The research was carried healthcare sector issuers listed on the Indonesia Stock Exchange (IDX). This research is a comparative quantitative. The members of the sample have been selected using purposive sampling and obtained 15 companies as samples. Data were analyzed using Wilcoxon Rank Test. The result shows that there is significant difference in stock return between before and during the covid-19 pandemic, this is supported by an increase in the profits of healthcare sector companies during the pandemic, meanwhile the TVA variable there is also a significant difference between before and during the covid-19 pandemic, this can be seen from the increase in transaction volume which shows investor interest in health-sector stock.